Psychometric Evaluation of the Revised Michigan Diabetes Knowledge Test (V.2016) in Arabic: Translation and Validation - Ali Hassan Alhaiti; Alanod Raffa Alotaibi; Linda Katherine Jones; Cliff DaCosta; George Binh Lenon (Journal of Diabetes Research)
Objective. To translate the revised Michigan Diabetes Knowledge Test into the Arabic language and examine its psychometric properties. Setting. Of the 139 participants recruited through King Fahad Medical City in Riyadh, Saudi Arabia, 34 agreed to the second-round sample for retesting purposes. Methods. The translation process followed the World Health Organization’s guidelines for the translation and adaptation of instruments. All translations were examined for their validity and reliability. Results. The translation process revealed excellent results throughout all stages. The Arabic version received 0.75 for internal consistency via Cronbach’s alpha test and excellent outcomes in terms of the test-retest reliability of the instrument with a mean of 0.90 infraclass correlation coefficient. It also received positive content validity index scores. The item-level content validity index for all instrument scales fell between 0.83 and 1 with a mean scale-level index of 0.96. Conclusion. The Arabic version is proven to be a reliable and valid measure of patient’s knowledge that is ready to be used in clinical practices.